2017
DOI: 10.3847/1538-4357/aa9cf1
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Study of the Magnetic Field Orientation in Solar Filaments

Abstract: We have carried out a statistical study of the average orientation of the magnetic field in solar filaments with respect to their axes for more than 400 samples, based on data taken with daily full-Sun, full-Stokes spectropolarimetric observations using the He I 1083.0 nm line. The major part of the samples are the filaments in the quiet areas, but those in the active areas are included as well. The average orientation of the magnetic field in filaments shows a systematic property depending on the hemisphere; … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…Spectropolarimetric observations using the He I 1083.0 nm line can provide a very useful diagnosis of magnetic field and flows in filaments and prominences. Hanaoka and Sakurai (2017) used data from full-disk 1083.0 spectropolarimetry to obtain a statistic evaluation of magnetic field orientation in filaments. Sasso et al (2014) analyzed the 1083.0 spectropolarimetric observation of an active region filament activated by a flare and found evidence of a coronal flux rope.…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…Spectropolarimetric observations using the He I 1083.0 nm line can provide a very useful diagnosis of magnetic field and flows in filaments and prominences. Hanaoka and Sakurai (2017) used data from full-disk 1083.0 spectropolarimetry to obtain a statistic evaluation of magnetic field orientation in filaments. Sasso et al (2014) analyzed the 1083.0 spectropolarimetric observation of an active region filament activated by a flare and found evidence of a coronal flux rope.…”
Section: Discussion and Future Prospectivementioning
confidence: 99%
“…Merenda et al (2007) studied the orientation of the magnetic field of a solar filament near disk center, and found that the inclination of the magnetic field is horizontal in the central part of the filament and changes along the filament axis, and its azimuth changes along the filament as well. Hanaoka, & Sakurai (2017) statistically studied the orientation of the magnetic field of filaments and confirmed their hemispheric pattern of chirality.…”
Section: Introductionmentioning
confidence: 86%
“…However, the statistical studies by Liu et al (2014) show that the hemispheric rule is followed only in 60% of cases. Therefore, in order to confirm the chirality and the axial orientation of the FRs we use other signatures such as pre-flare sigmoidal structures (Rust & Kumar 1996), J-shaped flare ribbons (Janvier et al 2014), coronal dimmings (Webb et al 2000;Thompson et al 2000;Gopalswamy et al 2018c), coronal cells (Sheeley et al 2013) or filament orientations (Hanaoka & Sakurai 2017). Analyzing the locations of the two core dimming regions or the two ends of the pre-flare sigmoidal structure, one can identify the locations of the two foot points of the FR.…”
Section: Direction Of the Axial Magnetic Field And The Sign Of Helicitymentioning
confidence: 99%